2022
DOI: 10.1186/s12284-022-00601-4
|View full text |Cite
|
Sign up to set email alerts
|

Wide Grain 3, a GRAS Protein, Interacts with DLT to Regulate Grain Size and Brassinosteroid Signaling in Rice

Abstract: Background: Grain size is a direct determinant of grain weight and yield in rice; however, the genetic and molecular mechanisms determining grain size remain largely unknown. Findings: We identified a mutant, wide grain 3 (wg3), which exhibited significantly increased grain width and 1000-grain weight. Cytological analysis showed that WG3 regulates grain size by affecting cell proliferation. MutMap-based gene cloning and a transgenic experiment dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Currently, with the development of genetics and genomics, genome-wide identification and analysis of the GRAS TF family has been completed in a variety of plants, including A. thaliana [ 27 ], O. sativa [ 28 ], Populus [ 29 ], pine [ 30 ], Avena sativa [ 31 ], and soybean [ 32 ]. The GRAS TF family has vital regulatory roles in plant growth and development [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, with the development of genetics and genomics, genome-wide identification and analysis of the GRAS TF family has been completed in a variety of plants, including A. thaliana [ 27 ], O. sativa [ 28 ], Populus [ 29 ], pine [ 30 ], Avena sativa [ 31 ], and soybean [ 32 ]. The GRAS TF family has vital regulatory roles in plant growth and development [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of OsDLT could suppress the phenotypes of OsGSK2 overexpression lines indicating that OsDLT functions downstream OsGSK2 in rice (Liu et al, 2021). Another GRAS transcription factor in rice, WIDE GRAIN3 (WG3), was shown to physically interact with Os DLT to promote BR signaling and increase grain size (Chen et al, 2022). Os DLT has also been implicated in GA metabolism as loss of function Osdlt mutants have reduced GA levels, reduced α-amylase activity in seeds, and upregulated GA biosynthetic gene transcripts (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple copies of 14-3-3 proteins in Arabidopsis and neither knock-out mutations nor RNAi lines resulted in any visible phenotypes, likely due to a redundancy in function across the multiple copies (Gampala et al, 2007). Studies have also shown that the At BES1/ At BZR1 transcription factors can be activated independently of the BR signaling pathway (Zheng et al, 2019; Albertos et al, 2022; Bai et al, 2022; Chen et al, 2022; Shi et al, 2022; Zheng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%